Transferring Peucedanum macilentum (Apioideae, Apiaceae) to Ligusticopsis based on morphological and molecular evidences - Niu, Junmei; Zhou, Ting; Li, Weixian; Zhou, Shilin; Liu, Zhenwen; Zhou, Jing (Phytotaxa, 2024)
Peucedanum macilentum is a less-studied species endemic to China, previously assigned to the genus Kitagawia. To elucidate its taxonomic affinity, morphological and molecular analyses were conducted. Morphologically, Peucedanum macilentum resembles Ligusticopsis species in several diagnostic characters of the stem base clothed in fibrous sheaths, pinnate bracteoles, conspicuous calyx teeth, strongly dorsally compressed fruits, as well as more vittae on the commissure. Phylogenetic analyses of nrDNA ITS and plastome sequences further reveal that P. macilentum is distant from Kitagawia but nested within Ligusticopsis. Therefore, in the basis of the morphological and molecular evidences, Peucedanum macilentum is transferred into Ligusticopsis and a new combination, Ligusticopsis macilenta, is proposed.